The Winter raven - Burtner, Matthew (Mnémothèque Internationale des Sciences et Arts en Musique Électroacoustique, 1999)
Recording of Matthew Burtner's The Winter raven. This recording is a collection of excerpts from a live performance of the opera. This is a large-scale multimedia composition for voice, instrumental ensemble, electronics, dance ensemble, video projection, and theatrical staging. The three act composition metaphorically connects an Inuit creation story, in which the world is created by "Raven" with snow, with the ecological seasonal approach of winter. Each act contains a chamber music piece with video and a "story" involving music, dance, and interactive video. This piece was inspired by the composers home in Alaska and was written as part of his dissertation at Stanford University. It premiered at the University of Virginia in 2003.